Dinâmica da tristeza parasitária bovina em um sistema intensivo de produção de leite em Minas Gerais - Leticia Camelo Vespasiano (2016)
The tick fever complex is responsible for major losses to the Brazilian livestock and knowledge of its epidemiology has become increasingly necessary. The aim of this study was to know the dynamics of infection by Anaplasma marginale, Babesia bovis and B. bigemina in Holstein calves in an intensive farming system. The experiment was conducted on a farm in the municipality of Inhaúma - Minas Gerais, which has a history of high rates of morbidity and mortality of animals in the growing phase for anaplasmosis and babesiosis. 224 animals were divided into seven groups were used. The evaluation was done by blood smear, packed cell volume, IFAT and PCR. The animals showed a period of increased susceptibility to anaplasmosis and babesiosis by B. bigemina during the growing phase. As for B. bovis drop of passive immunity occurred simultaneously with the development of active immunity. Were detected some cases of transplacental transmission of A. marginale and B. bovis. Babesia infections began in the post-house phase, during which the animals began to have contact with ticks. Infections with A. marginale had predominated during the growing phase. The fall of the packed cell volume and the largest number of anemic animals occurred in the major phase concentration of clinical cases of anaplasmosis and babesiosis. The results showed that young animals in this farm have susceptibility to A. marginale and B. bigemina. The situation for B. bovis is stable, and there may be some sporadic cases.